DETERMINATION OF PARAMETERS OF WHITE DWARF BY THE HYDROGEN SPECTRUM IN THE MODEL WITH LINEAR EQUATION OF STATE - Scherbakov, Christian (Одеські астрономічні публікації, 2013)
Solutions to Einstein’s ﬁeld equations, for a static spherically symmetric perfect fluid model with linear equation of state are found exactly. It is shown that space of WD can be presented as a space with deformed Heisenberg algebra so WD observational data provide powerful tool in deformed space research. Lane-Emden equation for isothermal model is considered in details.